Including the student with Autism Spectrum Disorder in early childhood education (Research, Society and Development, 2019)
The present study has as its foundation the trajectory of the difficulties of including the student with Autism Spectrum Disorder (ASD) in early childhood education and the challenges teachers to receive these students in the classroom. The choice of this is justification to deepen our knowledge as future pedagogues, improving even more the idea of inclusion in early childhood education. The purpose of this article is to understand the importance of student with ASD in early childhood education. The methodology consists of bibliographic research, articles, printed books, official documents of the Ministry of education. Discussed in this article study aspects that constitute the student with ASD in the classroom, educational strategies and the importance of inclusion. Since this article is aimed at how students with TEA are included in the children's classroom and the preparation of teachers that this can happen. So, this study is based on teacher training and in note to be prepared professionally, being a good mediator to prepare these students for the future. As relevance, it is important to emphasize the challenge of inclusion that should be fulfilled in every school day, because it's not only because that exists, but do happen, and the teacher as mediator, to understand all aspects involving this student to a constant socialization.